TOWARDS UNDERSTANDING THE CONCEPT OF “PUBLIC MANAGEMENT OF AGRICULTURAL LAND” - Velychko , L.; Rybalko , K. (Theory and Practice of Public Administration, 2021)
A comparative analysis of the essence of such concepts as “state governance”, “land management” and “public administration” has been carried out. The importance of formulating the concept of “public management of agricultural land” has been substantiated, and the concept of “public management of agricultural land” has been grounded for the conditions of land reform and decentralization reform, which is naturally related to the land resource potential of Ukraine, in particular in the realm of agricultural lands. International studies of the concept of “public administration” emphasize such aspect of this concept as involvement of not only public authorities but also local governments into fulfilling management functions in the public sphere. Such a scientific position is only gradually finding its place in the national school of public administration science, which is due to the reform of decentralization in Ukraine and the relevant developments in legislative activity.The significant land resource potential of Ukraine, in particular in the part of agricultural lands, which are the basic basis of land reform and decentralization reform, testifies to the importance of public management of such lands. Simultaneously with scientific developments in the formulation of the concept of public administration with an emphasis on the process of “privatization” of management, this position is influenced by legislative activity, which aims to regulate land relations in the country.According to the results of the study, it should be noted that the current state of development of significant land resource potential of Ukraine for agricultural lands, requires the formulation of appropriate terminology of such management, which would take into account the general conceptual framework of management, met the requirements of decentralization reform. developed legal framework and took into account the modern specifics of the powers of public authorities and local governments in the regulation of land relations. Given the following components, the concept of public management of agricultural land is a management activity of public authorities and local governments aimed at regulating land relations in agricultural land through the privatization of such management (land management, land management and land protection, control over the use and protection land, the provision of administrative services in the field of land relations, etc.).